Digital Drivers of Carbon Disclosure Quality in the Era of Mandatory Reporting - Rohaeni, Nani; Bratakusuma, Sumantri (Advances in Accounting Innovation, 2025)
Objective: This paper explores the impact of computerized reporting forms on the quality of corporate reporting.Methods: The research employs a quantitative method, utilizing secondary data from 140 mining sector companies listed on the Indonesia Stock Exchange. The data was a statistical software program, in order to evaluate the impact of Green Corporate Governance (GCG) as a moderator. Multiple regression and moderation testing were employed in this analysis.Results: The findings indicate that these digital technologies, including Digital Carbon Reporting, Digital Audit Trail, Digital Assurance, Digital Transparency, and Digital Governance Integration, exert a favorable influence on the quality of disclosure. In addition, GGC moderated the association of the components of digital reporting with the level of disclosure, with the exception of the component of digital assurance, for which the role of moderation was statistically insignificant.Novelty: This study makes two novel contributions to the extant literature. Firstly, it is the first study to introduce digital accounting innovations into the existing body of literature on sustainability governance frameworks. This is a critical but under-researched area, particularly in the context of emerging markets. This "addresses the role of GCG as a strategic moderator enhancing the effectiveness of online financial and non-financial disclosure mechanisms." The research contributes to extant work on stakeholder accountability and digital assurance more generally in the wider ESG reporting space.Research Implications: This study provides empirical evidence regarding the relevance of integrating GCG into digital reporting formats, with respect to greater transparency, lower information asymmetry, and convergence of sustainable accounting standards for regulators, auditors, and corporate management.